2022
DOI: 10.3389/fped.2022.803408
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Thromboembolism After Fontan Surgery: Considerations for Thromboprophylaxis

Abstract: The Fontan circulation introduces an increased risk of thromboembolism which is associated with substantial mortality and morbidity. Adverse outcomes of thromboembolic complications post-Fontan surgery vary in both nature and severity, ranging from local tissue infarction and pulmonary embolism to Fontan failure and ischemic stroke. Furthermore, recent studies have identified that subclinical stroke is common yet underdiagnosed in Fontan patients. Fontan patients are commonly treated with antiplatelet agents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…single ventricle disease after Fontan type operation, are at a particular high risk of thromboembolism due to endothelial dysfunction, abnormal blood flow, and hypercoagulable state resulting from the unique hemodynamic pattern and associated liver dysfunction 28 . Previous studies have reported rates of thromboembolism and stroke as high as 19%, with subclinical stroke detected through magnetic resonance imaging even more common 28,29 . The Australia national registry study showed that the free-from-thromboembolism rate 25 years after Fontan operation is 82% 30 .…”
Section: Cva and Outcome In Af With Achdmentioning
confidence: 99%
“…single ventricle disease after Fontan type operation, are at a particular high risk of thromboembolism due to endothelial dysfunction, abnormal blood flow, and hypercoagulable state resulting from the unique hemodynamic pattern and associated liver dysfunction 28 . Previous studies have reported rates of thromboembolism and stroke as high as 19%, with subclinical stroke detected through magnetic resonance imaging even more common 28,29 . The Australia national registry study showed that the free-from-thromboembolism rate 25 years after Fontan operation is 82% 30 .…”
Section: Cva and Outcome In Af With Achdmentioning
confidence: 99%